Needs for care among patients with schizophrenia in six European countries - Kovess-Masféty, Viviane (2017)
Background: This article compares needs for care among patients with schizophrenia across six European countries and examines how this relates to the diversity of psychiatric systems in Europe. Methods: A one-year prospective cohort study was set up. Inclusion criteria for patients were: a clinical lifetime diagnosis of schizophrenia according to ICD-10 (F20) diagnostic criteria for research, age between 18 and 65 years and at least one contact with mental health services in 1993. The patients were assessed for their clinical diagnosis and symptoms using the SCAN interview (Schedules for Clinical Assessment in Neuropsychiatry) and the interventions proposed to them were recorded through the systematic use of the NFCAS (Needs For Care Assessment Schedule). Results: 438 patients were included and 391 were followed up. The mean age was 38 years, the mean age at onset was 22 years, and 59% were out-patients, 24% in day care and 15% hospitalized. The populations in the different centres were significantly different for almost all the variables: sociodemographic, clinical and social, and the problems identified remained relatively stable over the year. Comparisons highlighted cultural differences concerning the interventions that were proposed. Centres in Italy, Spain and Portugal proposed many interventions even though they were relatively deprived in terms of resources, and the tendency seems to be the reverse for the Northern European countries. On average, one in four patients suffered from needs that were not adequately met by the mental health service in their region. These needs (on average 6 per patient) varied from psychotic symptoms to managing their own affairs. The number of interventions was not correlated to the need status. The availability of community-based treatment, rehabilitation and residential care seems to predict smaller proportions of patients with unmet needs. Conclusion: There appeared to be a systematic relationship between the availability of community-based mental health care and the need status of schizophrenic patients: the fewer outpatient and rehabilitation services available, the more unmet needs there were.